Proceedings of the 12th ACM International Conference on Ubiquitous Computing 2010
DOI: 10.1145/1864349.1864391
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting on-screen instructions with micro-projected guides

Abstract: We present a study that evaluates the effectiveness of augmenting on-screen instructions with micro-projection for manual task guidance unlike prior work, which replaced screen instructions with alternative modalities (e.g., headmounted displays). In our study, 30 participants completed 10 trials each of 11 manual tasks chosen to represent a set of common task-components (e.g., cutting, folding) found in many everyday activities such as crafts, cooking, and hobby electronics. Fifteen participants received only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In 2010 a study first evaluated the effectiveness of augmenting on-screen instructions with microprojection for manual task guidance [9]. It focused on everyday tasks performed by un-impaired users and showed that the augmented instructions improved overall participants' performance.…”
Section: Related Workmentioning
confidence: 99%
“…In 2010 a study first evaluated the effectiveness of augmenting on-screen instructions with microprojection for manual task guidance [9]. It focused on everyday tasks performed by un-impaired users and showed that the augmented instructions improved overall participants' performance.…”
Section: Related Workmentioning
confidence: 99%
“…The user study setup in the worker's area with either the helmet configuration (top) or tripod (middle) and the remote expert's area (bottom). Four magnetic whiteboards were arranged in a box-like formation similar to the 'Trace Shape" and "Mark Locations" activities investigated by Rosenthal et al (2010), and the drawing/cutting/placing activity employed by Stevenson et al (2008).…”
Section: Taskmentioning
confidence: 99%
“…In order to do that, they had to pick up the correct objects -among the objects distributed around the room-and place them in the correct positions on a grid. The tasks selected for this study have the following properties: Accordingly, we selected this particular puzzle activity from the nine categories for manual tasks referenced in [11], however we normalized it to assess the quality of non-sequentially and spatial distribution of situated micro-displays. The independent variable of the study is the number of micro-displays.…”
Section: User Studymentioning
confidence: 99%